Preliminary results of Resistive Plate Chambers operated with eco-friendly gas mixtures for application in the CMS experiment. (27th September 2016) - Abbrescia, M.; Auwegem, P. Van; Benussi, L.; Bianco, S.; Cauwenbergh, S.; Ferrini, M.; Muhammad, S.; Passamonti, L.; Pierluigi, D.; Piccolo, D.; Primavera, F.; Russo, A.; et al.
Abstract: The operations of Resistive Plate Chambers in LHC experiments require Fluorine based (F-based) gases for optimal performance. Recent European regulations demand the use of environmentally unfriendly F-based gases to be limited or banned. In view of the CMS experiment upgrade, several tests are ongoing to measure the performance of the detector with these new ecological gas mixtures, in terms of efficiency, streamer probability, induced charge and time resolution. Prototype chambers with readout pads and with the standard CMS electronic setup are under test. In this paper preliminary results on performance of RPCs operated with a potential eco-friendly gas candidate 1, 3, 3, 3-Tetrafluoropropene, commercially known as HFO-1234ze, with CO 2 and CF 3 I based gas mixtures are presented and discussed for the possible application in the CMS experiment.